The influence of job stress, job satisfaction, and organizational commitment on turnover intention of accounting and finance employees at PT. Multi Nabati Sulawesi - Fajriansyah, Yudi; Kalangi, Lintje; Lambey, Robert (Yayasan Widyantara Nawasena Raharja, 2024)
Turnover intention is an intention or desirability from a person as an employee to quit, stop, or move from his job. Turnover intention becomes one of the problems which often happen in a company as it can disadvantage or bother work activities in company. This study aims to test and analyze the influence of job stress, job satisfaction, and organizational commitment on turnover intention. This type of research is quantitative research that uses research instruments, quantitative/statistical data analysis with the aim of testing hypotheses. The population in this study is 36 people in the accounting and finance department who work at PT. Multi Nabati Sulawesi. The data analysis method used in this study is descriptive statistical analysis, instrument test, classical assumption test, and hypothesis test using SPSS software version 24. The result of the research shows that (1) work stress has a positive effect on turnover intention, meaning the lower the perceived work stress, the lower the desire to switch jobs, and conversely, the higher the level of work stress, the higher the tendency to switch jobs. (2) job satisfaction has a negative effect on turnover intention, meaning the higher the level of job satisfaction of employees, the lower their tendency to switch jobs, and conversely, the lower the job satisfaction perceived, the higher the desire to switch jobs. (3) organizational commitment doesn’t have an effect on turnover intention.